Exploring Ethnomathematics to Gayasan Tobacco Warehouse at Jember, East Java, Indonesia - Akbar, Ahmad Maulana; Marsidi, Marsidi; Putra, Eric Dwi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
Ethnomathematics which link culture with community activities, certainly has characteristics that support each other with mathematical concepts. Ethnomathematics is mathematics practiced by specific cultural groups in society. This study examines the mathematical concepts in the Gayasan tobacco warehouse building in Jenggawah District, Jember Regency. In the study, researchers used qualitative descriptive research with an ethnographic approach. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are done through data reduction, presentation, analysis, and exposure. The results showed that in the Gayasan tobacco warehouse, Jenggawah District, Jember Regency, there are mathematical concepts that will be studied further in the future. The author focuses on applying geometric concepts such as building flat, building space, lines, angles, number patterns, congruence, and awakening in research. Each longkang is bordered with bamboos that function as poles, also known as